Penerapan Akuntansi dan Digitalisasi Marketing sebagai Upaya Peningkatan Omset Usaha di Pondok Laundry Ubud: Pengabdian - Ni Made Intan Kusumasari; Putu Ayu Trisna Febrianty; Christina Ayu Maha Dewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service activity aims to provide comprehensive training on the application of accounting through simple bookkeeping and digital marketing for the business owners of Pondok Laundry Ubud. Through field observations and interviews, it was found that the main problems faced by Pondok Laundry Ubud include a lack of knowledge in preparing financial reports and implementing effective digital marketing strategies. Therefore, this activity is expected to enhance the understanding of the business owners so that they can utilize existing potential more optimally in line with increasingly rapid developments. One of the efforts undertaken focuses on two main aspects, namely simple bookkeeping and online marketing. The results of this community service indicate that: (1) business actors are able to prepare simple bookkeeping and identify the actual financial condition of their business; (2) owners understand the importance of systematic financial recording and reporting; (3) after participating in the training, owners are able to apply bookkeeping to determine monthly profits and losses and plan financial strategies for the following period more effectively; (4) there is an increased understanding of online marketing concepts that can help them reach a wider customer base; and (5) the training equips laundry business owners with skills to utilize digital platforms more effectively for business promotion.